Solitary fibrous tumor of the greater omentum: case report and review of literature - Karim M. Eltawil; Carly Whalen; Bryce Knapp (Surgical Case Reports)
Abstract Background Solitary fibrous tumor (SFT) is a rare neoplasm of mesenchymal origin occurring most often in the visceral pleura, however, it has been described in almost every anatomic location of the human body. While most SFTs have a benign behavior, they can potentially be locally aggressive and demonstrate a malignant behavior. Case presentation A 63 year-old male patient presented with lower abdominal pain and nausea and was noted on CT to have a large, heterogeneous lower abdominal mass with no evidence of metastatic disease. A surgical resection was performed and the mass appeared to be connected to the greater omentum with a vascular pedicle. It was not invading any intra-abdominal or pelvic organs. Pathology revealed an SFT of omental origin. The mitotic count was less than 4 per 10 high-power fields and all pathologic characteristics did not meet the criteria for a malignant SFT. Conclusions We report an extremely rare case of SFT originating from the greater omentum. A multidisciplinary team approach was followed to plan the patient’s management strategy.